Effects of the association of diabetes and pulmonary emphysema on cardiac structure and function in rats. Issue 5 (29th October 2015) - Di Petta, Antonio; Simas, Rafael; Ferreira, Clebson L.; Capelozzi, Vera L.; Salemi, Vera M. C.; Moreira, Luiz F. P.; Sannomiya, Paulina
Summary: Chronic obstructive pulmonary disease is often associated with chronic comorbid conditions of cardiovascular disease, diabetes mellitus and hypertension. This study aimed to investigate the effects of the association of diabetes and pulmonary emphysema on cardiac structure and function in rats. Wistar rats were divided into control non‐diabetic instilled with saline (CS) or elastase (CE), diabetic instilled with saline (DS) or elastase (DE), DE treated with insulin (DEI) groups and echocardiographic measurements, morphometric analyses of the heart and lungs, and survival analysis conducted 50 days after instillation. Diabetes mellitus was induced [alloxan, 42 mg/kg, intravenously (iv)] 10 days before the induction of emphysema (elastase, 0.25 IU/100 g). Rats were treated with NPH insulin (4 IU before elastase plus 2 IU/day, 50 days). Both CE and DE exhibited similar increases in mean alveolar diameter, which are positively correlated with increases in right ventricular (RV) wall thickness ( P = 0.0022), cavity area ( P = 0.0001) and cardiomyocyte thickness ( P = 0.0001). Diabetic saline group demonstrated a reduction in left ventricular (LV) wall, interventricular (IV) septum, cardiomyocyte thickness and an increase in cavity area, associated with a reduction in LV fractional shortening ( P < 0.05), and an increase in LViv relaxation time ( P < 0.05). Survival rate decreased from 80% in DS group to 40% in DE group. In conclusion, alloxan diabetes did not affect RV hypertrophy secondary to chronic emphysema, even in the presence of insulin. Diabetes per se induced left ventricular dysfunction, which was less evident in the presence of RV hypertrophy. Survival rate was substantially reduced as a consequence, at least in part, of the coexistence of RV hypertrophy and diabetic cardiomyopathy.